VD_FINDINFO AI 185/09 - 85/2012 vom 9. Februar 2012 - VD Tribunal cantonal (2012)
ÉVALUATION DE L'INCAPACITÉ DE TRAVAIL, RENTE D'INVALIDITÉ, FORCE PROBANTE | 28 LAI, 4 al. 1 LAI, 16 LPGA, 6 LPGA, 7 LPGA, 8 al. 1 LPGA